Disparitas Kompetensi Guru dan Tantangan Profesionalisme di Era Kecerdasan Buatan - Namamta Azzahra; Vicxy Aning Agustine; Moh. Faizin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The rapid development of Artificial Intelligence (AI) in education presents both opportunities and challenges for teachers in carrying out their professional roles. Teachers are required not only to possess pedagogical and professional competencies but also to have the ability to adapt to continuously evolving digital technologies. However, in practice, there are still disparities in teacher competence influenced by factors such as unequal access to technology, age differences, and limited relevant training. This study aims to analyze the forms of disparities in teacher competence and the challenges faced in maintaining professionalism in the era of artificial intelligence. The method used is a library research approach by reviewing various relevant scientific literature sources. The findings indicate that disparities in competence have a significant impact on the quality of learning, particularly in the optimal use of AI-based technologies. Therefore, strategic efforts are needed to enhance teachers’ digital competence through continuous professional development, equitable access to technology, and strengthening AI literacy so that its utilization can be carried out wisely, ethically, and effectively in supporting the learning process in the digital era.